Om chanting modulates the processing of negative stimuli: Behavioral and electrophysiological evidence - Zhang, Ziyu; Peng, Yanqin; Chen, Tingji (Frontiers in Psychology, 2022)
Previous studies have suggested that Om chanting, as a type of meditation, can relieve individuals’ negative emotions. However, the dynamic aspects of neural processes in processing of the negative stimuli while Om chanting are still unclear. In this study, we recruited 33 healthy undergraduate students without meditation experience and recorded event-related potentials (ERPs) to unpleasant and neutral images when they performed Om chanting and viewing task. The behavioral results showed that the unpleasant images were rated as less unpleasant and arousing in the condition of Om chanting vs. passive viewing and the rates were not different between the two conditions for the neutral images. Analyses of the ERP responses to the emotional stimuli revealed that Om chanting decreased P1 and late positive potential (LPP) amplitudes for the neutral images but not for the unpleasant images. We speculated that Om chanting might reduce vigilance to the neutral stimuli, whereas for the negative stimuli, they automatically captured all available attentional resources and led to a failure in observing the regulating effect of Om chanting. These observations suggest that Om chanting modulates individuals’ affective evaluations to the negative stimuli and alters early visual and late neural processing of the stimuli.